A Study on Evaluation of Anti-Emetics in the Prevention of Chemotherapy Induced Nausea and Vomiting in Cancer Patients in A Tertiary Care Hospital - Paul, Elizabeth Phoeba; Behanan, Ahana; Eapen, Babitha Annie; James, Apollo; Sherief, Sheik Haja; Palanisamy, Mohanraj Kathirampatti; Sivakumar, Thangavel (Indian Journal of Pharmacy Practice)
Background: The contemporary lifestyle has made Cancer as one of the most deadly diseases. Treatment modalities of cancer are many, while chemotherapy seems to be the most common. Though, chemotherapy subsides the disease, it has many side effects in which Chemotherapy induced Nausea and Vomiting (CINV) is frequent. This study aims to evaluate various antiemetics in the prevention of Chemotherapy induced Nausea and Vomiting in cancer patients specifically in Breast, Lung, Cervix and Head & Neck cancers so that the rate of emesis, efficacy and comparative efficacy of different antiemetic combinations in cancer patients can be determined. Methods: A prospective observational study was carried out at a tertiary care hospital in Tamilnadu, South India between January to June, 2015 in which 241 cancer patients receiving antiemetics in their prescriptions meeting our inclusion criteria were analyzed using standard guidelines. A well designed data collection form was prepared to collect the datas. Results: It was observed from our study that the efficacy of different combination of antiemetics, mostly given as triple based regimen, relied on the treatment regimen of the particular cancer, thereby its emetogenic level and NCI-CTC grading score and it was found out that Ramosetron based triple antiemetic regimen was slightly better than Granisetron based regimen to control CINV. Conclusion: It is the need of the h to promote optimal antiemetic medication and ensure that cancer patient receives evidence-based, effective treatments for their health problems.
Keywords: CINV; Antiemetics; Breast cancer; Lung cancer; Cervical cancer; Head & Neck cancer